2010
DOI: 10.1177/0011000010369497
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Counseling and Psychotherapy in Schools: A Meta-Analytic Review of Treatment Outcome Studies 1Ψ7

Abstract: This study investigated the efficacy of counseling and psychotherapy interventions for youth in schools. Data were examined for 107 studies that included 132 treatment interventions. Overall efficacy was d = 0.45 and was significantly different from zero. Interventions for adolescents outperformed those of children, treatment groups that were predominately female or male did better than mixed-gender groups, and licensed professional therapists outperformed paraprofessionals, who outperformed graduate students.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
54
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 117 publications
2
54
0
5
Order By: Relevance
“…The American School Counselor Association reported that, in the 2009Á2010 school year, there was one school counselor for every 459 students across the USA (National Center for Education Statistics, 2011). School-based counseling interventions have been found to lead to significant improvements in mental wellbeing, with a mean effect size (ES, d) of 0.45 (95% CI: 0.37 Á 0.53) (Baskin et al, 2010). This compares with ESs of between 0.7 and 0.8 for most adult psychotherapy interventions (Lambert & Ogles, 2004), and is towards the lower end of the overall ESs found in meta-analyses of therapeutic interventions for children and young people: 0.45 to 0.7 (Kazdin, 2004;Weisz, Weiss, Han, Granger, & Morton, 1995).…”
mentioning
confidence: 99%
“…The American School Counselor Association reported that, in the 2009Á2010 school year, there was one school counselor for every 459 students across the USA (National Center for Education Statistics, 2011). School-based counseling interventions have been found to lead to significant improvements in mental wellbeing, with a mean effect size (ES, d) of 0.45 (95% CI: 0.37 Á 0.53) (Baskin et al, 2010). This compares with ESs of between 0.7 and 0.8 for most adult psychotherapy interventions (Lambert & Ogles, 2004), and is towards the lower end of the overall ESs found in meta-analyses of therapeutic interventions for children and young people: 0.45 to 0.7 (Kazdin, 2004;Weisz, Weiss, Han, Granger, & Morton, 1995).…”
mentioning
confidence: 99%
“…A meta-analysis (Baskin et al, 2004) of a range of interventions (predominantly cognitive behavioural therapies) using a wide range of measures showed a significant effect with a mean weighted effect size of 0.45. The effect size is way of expressing the difference between two groups, or the same group before and after an intervention.…”
mentioning
confidence: 99%
“…Reason for exclusion Barlow, smailagic, Ferriter, Bennett, and Jones (2010) too few school-based studies on outcomes of interest included Baskin et al (2010) Unclear if outcomes of interest were included in review, and if they were to what extent Beelmann and Raabe (2009) Review of reviews Protocol of a review, not an actual review Bowman-Perrott, Burke, nan, and Zaini (2014) too few school-based studies on outcomes of interest included candelaria, Fedewa, and ahn (2012) could not clearly determine all of the studies which were school-based and which considered outcomes of interest cobb, sample, Morgen, and Johns (2006) could not clearly determine all of the studies which were school-based and which considered outcomes of interest edwards and hinsz (2014) too few school-based studies on outcomes of interest included ehiri, hitchcock, ejere, and Mytton (2007) Protocol of a review, not an actual review Fellmeth, heffernan, nurse, habibula, and sethi (2013) could not clearly determine which studies that were included in analysis were school-based Ferguson, Miguel, Kilburn, and sanchez (2007) effects for bullying and other types of violence were not reported separately. could not determine extent to which violence outside of bullying was represented in statistics grove, evans, Pastor, and Mack (2008) could not clearly determine how many school-based interventions were included, and thus how represented they were in the statistics R. hahn et al (2007) a published version of this report was also found in our searches and thus used instead.…”
Section: Appendix B References Of Included Reviewsmentioning
confidence: 99%